2017
DOI: 10.1136/archdischild-2017-312808
|View full text |Cite
|
Sign up to set email alerts
|

Nasal midazolam vs ketamine for neonatal intubation in the delivery room: a randomised trial

Abstract: This clinical trial was recorded on the National Library of Medicine registry (NCT01517828).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…There is general consensus that an infant should be adequately sedated when an endotracheal intubation procedure is performed 9–12. Although it is known that visualising the vocal cords with a laryngoscope is highly uncomfortable,13 there is still no consensus on whether or not to use sedation during MIST, particularly when a laryngoscope is used.…”
Section: Introductionmentioning
confidence: 99%
“…There is general consensus that an infant should be adequately sedated when an endotracheal intubation procedure is performed 9–12. Although it is known that visualising the vocal cords with a laryngoscope is highly uncomfortable,13 there is still no consensus on whether or not to use sedation during MIST, particularly when a laryngoscope is used.…”
Section: Introductionmentioning
confidence: 99%
“…A report from the AAP on premedication for non-emergency endotracheal intubation in the neonate stated that midazolam should not be used in preterm infants, but it can be considered for use in the term or older infant as part of the premedication sequence for elective intubation in the NICU 8. Notwithstanding the discouraging results of previous studies, a recent randomised trial assessed nasal administration of midazolam (nMDZ) and concluded that nMDZ was more effective than nasal ketamine to adequately sedate neonates requiring intubation in the delivery room 26. The haemodynamic and respiratory effects of both drugs were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…If a venous line is not available, despite every effort having been made to establish an intravenous line, especially in the delivery room, consider using a maximum of two doses of intranasal midazolam (0.2 mg/kg) (50). Low quality of evidence.…”
Section: Endotracheal Intubationmentioning
confidence: 99%
“…One study showed that nasal midazolam provided rapid and effective sedation to intubated neonates in the delivery room (44). Another study showed a lower efficacy of nasal ketamine (2 mg/kg) compared to nasal midazolam (0.2 mg/kg), but similar side effects, in preterm neonates requiring nonemergency endotracheal intubation for surfactant instillation in the delivery room (50). There is no available data at the moment on any other drug used for pain control during endotracheal intubation in infants.…”
Section: Appendix 3: Further Work On the Subject Of Analgesia And Sedmentioning
confidence: 99%
See 1 more Smart Citation